2019
DOI: 10.1007/s12187-019-09648-0
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationship Among Bullying, School Climate and Adolescent Well-Being in Chile and South Africa: a Cross Cultural Comparison

Abstract: Bullying at school represents a major challenge in different school cultural contexts. As a result, victims of bullying experience negative consequences that influence their daily life and personal well-being. School climate in particular is important to consider in the prevention of bullying and its consequences. However, few studies have examined the effects of bullying victimization on children's subjective well-being (SWB), using hierarchical analysis, in different cultural contexts. Therefore, the current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 84 publications
0
8
0
2
Order By: Relevance
“…A study using the second wave of the Children’s Worlds project showed that children who had been bullied had significantly lower SWB than those who had not (Bradshaw et al, 2017 ). A study in Chile and South Africa also showed a negative relationship between bullying victimisation and SWB (Varela et al, 2020 ), as well as a study in Algeria (Tiliouine, 2015 ).…”
mentioning
confidence: 84%
“…A study using the second wave of the Children’s Worlds project showed that children who had been bullied had significantly lower SWB than those who had not (Bradshaw et al, 2017 ). A study in Chile and South Africa also showed a negative relationship between bullying victimisation and SWB (Varela et al, 2020 ), as well as a study in Algeria (Tiliouine, 2015 ).…”
mentioning
confidence: 84%
“…For example, bullying and cyberbullying victims show lower levels of subjective wellbeing than non-victims, and victimization is negatively related to wellbeing at these ages (Chai et al, 2020 ; Miranda et al, 2019 ). When observing the effects of victimization on adolescent subjective wellbeing in different cultural contexts (Chile and South Africa), bullying is observed to be a significant predictor of subjective wellbeing at the individual and school levels in both cultural contexts (Varela et al, 2020 ). It should be noted that the negative relationship between bullying and subjective wellbeing is seen across age groups and geographical populations (Savahl et al, 2019 ).…”
Section: Victimization and Adolescent Wellbeing During The Covid-19 Pandemicmentioning
confidence: 99%
“…The study indicated the combined influence of physical and psychological bullying contributes significantly and negatively to SWB across age groups and geographical, cultural populations. Moreover, bullying has negative emotional, physical, and behavioural effects on victims' well-being (Saiz et al, 2019;Skrzypiec et al, 2019;Varela et al, 2020). More specifically, studies have shown being bullied by peers is strongly and consistently associated with several mental health problems, such as personal distress and depressive mood, anxiety, increased fear, diminished sense of belonging, social isolation, low self-esteem, school avoidance, social anxiety, and psychoactive substance abuse (Fitzpatrick & Bussey, 2011;V.…”
Section: Bullying and Well-beingmentioning
confidence: 99%